2013
DOI: 10.1002/pc.22485
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite of polyaniline and a layered niobate acid host: Synthesis, electrochemical studies, and photocatalytic properties

Abstract: The synthesis of polyaniline (PANI) with H 4 Nb 6 O 17 (HNbO) to form PANI/HNbO lamellar nanocomposite by in situ polymerization using aniline (ANI) intercalation compound ANI/HNbO as the intermediate has been investigated. The properties of the samples were characterized by means of XRD, SEM, TEM, FT-IR, UV-vis spectroscopy, and TG-DTA. The in situ polymerization of ANI packed in a regular orientation in a mono-and bilayers (i.e., pseudo-bilayers) structure within the HNbO interlayers led to PANI/HNbO nanocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…A series of n-alkoxy hybrids with organic chains containing n = 1, 3, 6, 10, 18 carbon atoms has been tested and it was shown that, unlike short-chain alcohols, modification by long-chain alcohols (n = 10, 18) significantly improves the photocatalytic activity of the samples. Another example of the preparation of hybrid catalysts based on niobates and titanates is polyaniline-intercalated compounds which proved themselves as effective catalysts in the visible light region in the decomposition of methylene blue reaction (Guo et al, 2010;Zhu et al, 2013;Liu et al, 2014). Such hybrids have also been obtained from some other layered perovskite-like oxides, though their photocatalytic activity has not been studied (Uma and Gopalakrishnan, 1994;Uma et al, 1995;Tong et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A series of n-alkoxy hybrids with organic chains containing n = 1, 3, 6, 10, 18 carbon atoms has been tested and it was shown that, unlike short-chain alcohols, modification by long-chain alcohols (n = 10, 18) significantly improves the photocatalytic activity of the samples. Another example of the preparation of hybrid catalysts based on niobates and titanates is polyaniline-intercalated compounds which proved themselves as effective catalysts in the visible light region in the decomposition of methylene blue reaction (Guo et al, 2010;Zhu et al, 2013;Liu et al, 2014). Such hybrids have also been obtained from some other layered perovskite-like oxides, though their photocatalytic activity has not been studied (Uma and Gopalakrishnan, 1994;Uma et al, 1995;Tong et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One can also note interesting results obtained for layered oxides intercalated by polyaniline. Such hybrids have shown themselves to be effective photocatalysts in the visible spectral region, having been tested on the model decomposition reaction of methylene blue dye (Guo et al, 2010;Zhu et al, 2013;Liu et al, 2014). Although aniline-intercalated compounds have also been obtained for layered perovskite-like oxides Gopalakrishnan, 1994, 1995;Tong et al, 2005), the photocatalytic activity of such hybrids has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the comparison of FTIR spectra of P(2,3‐DMA), PANI, P(2,3‐DMA)/PANI composite, and P(2,3‐DMA)/PANI blend, in which the composite was synthesized under the ratio of aniline (AN)/P(2,3‐DMA) = 18/5. It can be seen that all the samples have similar characteristic peaks at 3,450–3,440, 1,585–1,560, 1,480, 1,320–1,300, 1,250–1,240, 1,140–1,130 cm −1 , which are, respectively, assigned to NH stretching vibration of secondary amino group (NH) , quinoid (Q) ring‐stretching , benzene (B) ring‐stretching , CN stretching of the secondary aromatic amine , CN stretching vibration in the polaron structure , and aromatic CN in‐plane bending . However, there are still significant differences among these samples.…”
Section: Resultsmentioning
confidence: 98%